University proceedings. Volga region. Social sciences - Legislation on the rights of indigenous small-numbered peoples of the Russian Federation: current situation and some development trends (Известия высших учебных заведений. Поволжский регион: Общественные науки)
Background. For centuries, the Russian State has pursued a policy of supporting various aspects of Indigenous Small-numbered Peoples’ life. The need for a special policy is essential given their unique situation characterized by a scant population, as well as the fragility of their traditional lifestyle and support systems. The objective of this study is to examine the situation and discern the evolutionary trajectory of legal frameworks designed to safeguard the rights of these communities. Materials and methods. Conduction of the research tasks was achieved by the examination of the pertinent constitutional provisions in the Russian Federation’s Constitution, as well as review of both federal and regional legal frameworks concerning the Russian Federation’s Indigenous Small-numbered Peoples. Additionally, specific strategic planning documents, encompassing various strategies and concepts were analyzed. Within the framework of this research, general scientific and spe-cial methods were used, including analysis, synthesis, historical and formal-legal methods. Results. The legislative framework that pertains to the rights of Indigenous Small-numbered Peoples is dual-layered which was evolved over time, demonstrating a historical progres-sion in the laws that recognize and protect the unique legal status of these communities. The consideration has been given to both the current state and the future trajectory of such legislation. Conclusions. Federation’s legislation on the rights of Indigenous Small-numbered Peoples contains core standards, while regional legislation makes it possible to specify and supplement these standards and take into account the specific characteristics of the region. Recognition of the special legal status of Indigenous Small-numbered Peoples is a key aspect of Russian legislation. This includes both individual and collective rights, in particular the right to determine their own priorities for development, as well as the preser-vation of their identity and cultural and linguistic diversity. In this context, the legislation aims to support and protect not only the rights to traditional ways of life, but also to provide them with opportunities for progressive sustainable development in accordance with their own values and interests, which allows to adapt to modern challenges.